A LIFELONG LEARNING AS AN INCENTIVE OF LEADERSHIP: KEY ELEMENT IN LEADERSHIP DEVELOPMENT - Sotiroska, Kalina; Filipovski, Zoran; Kahveci, Müedin (International Scientific Journal Vision, 2019)
Lifelong learning is an important factor in leadership development. This article addresses the relationship between lifelong learning and leadership. There were asked 60 participants about lifelong learning. The obtained findings of the study contribute to theory of leadership, lifelong learning and could help in the process of improving the society. A leadership development program can incorporate the findings of theories of learning and improve implementation of the knowledge in everyday life.